2005
DOI: 10.1111/j.1348-0421.2005.tb03693.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Anaphylatoxins to Allergic Inflammation in Human Lungs

Abstract: The contribution of complement activation to allergic asthma remains controversial. In order to elucidate the role played by the complement split products, anaphylatoxins C3a and C5a, we evaluated their effects on production of cysteinyl‐leukotrienes (cysLTs) by human lung fragments following an anaphylactic reaction. The lung tissues obtained from two patients with lung cancer showed C5aR‐, C5L2R‐, and C3aR‐mRNA expression. When the chopped lung fragments passively sensitized with human IgE were incubated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…murine BM derived DC, human monocyte derived DC) in response to pathogenic or inflammatory stimuli (e.g. LPS, interferons, prostaglandin E 2 ) [11,23,24], and in inflamed lung tissues [22,[32][33][34][35]. These findings imply the roles for C3aR and C5aR in inflammatory and immunological diseases.…”
Section: C3ar and C5ar Expressionmentioning
confidence: 81%
“…murine BM derived DC, human monocyte derived DC) in response to pathogenic or inflammatory stimuli (e.g. LPS, interferons, prostaglandin E 2 ) [11,23,24], and in inflamed lung tissues [22,[32][33][34][35]. These findings imply the roles for C3aR and C5aR in inflammatory and immunological diseases.…”
Section: C3ar and C5ar Expressionmentioning
confidence: 81%
“…These results suggested that AcPepA is more resistant to proteases from neutrophils than PepA. Recently, we demonstrated in preliminary experiments with human lung tissues that AcPepA could interfere with C5a function to enhance cysteinyl-leukotrienes (1).…”
Section: Discussionmentioning
confidence: 95%
“…Primers for ␤-actin, C4, and CXCL8 (IL-8) have been published earlier (see Table 1). The deoxynucleotide primer sequences for factor B and C5aR were obtained from existing publications (2,46). Primers for C5 and C5L2 were designed from cDNA sequences (reference nos.…”
Section: Methodsmentioning
confidence: 99%